THE AUDIO VIDEO OF WEB-BASED COMPRESSION WITH FFMPEG - Triantoro, Afrizal; Sajati, Haruno; Pujiastuti, Asih (Compiler, 2018)
In general, video compression only compresses video files without compressing the audio files in them. This results in the compression process not being maximized.This study discusses the process of compressing video and audio files to get maximum compression. The application built is a web-based video compression software utilizing FFmpeg to do the compression process by breaking down the original video which has a resolution of 720 to 4 files, namely 720, 480, 360, and 240 resolutions. The test is done by comparing the compression results only to video files and compressing to video and audio and there is a 1-2 MB file size difference, whereas when compared to the original file, there is a 5-20 MB size difference. In addition to conducting this test also performed compression testing on different devices and obtained relatively similar results on all devices. Test the image quality on the compressed file obtained the image quality results in the standard video compression below 30dB results.